Åndens hermeneutik. En læsning af I al sin Glands nu straaler Solen - Hansen, Jakob Ulrik (Grundtvig-studier, 2011)
Åndens hermeneutik. En læsning af “I al sin Glands nu straaler Solen ”[The hermeneutics of the Spirit. A reading of “I al sin Glands nu straaler Solen ”]By Jakob Ulrik Hansen This article takes as its point of departure the question of how Grundtvig in his hymns seems to amalgamate the seasons, the biblical world, legendary material and historical events without reflecting on time. Through a reading of “I al sin Glands nu straaler Solen” (In all its Splendour now the Sun shines), the article discusses what enables this particular form of poetic hermeneutics.The blending of early-summer sun with divine light “ Glands” (splendor or doxa) in the beginning of the hymn generates a vision of the world in two levels, which becomes constitutive of the entire hymn. In the following stanza, summer becomes an image of the recovered connection with Paradise through the Pentecostal spirit, e.g. in the breeze through the leaves and the rippling water in the creek. This divine affiliation of the natural phenomena is indicated by various allusions to their provenance in Paradise. The centre of the hymn, stanza 4, relates how the spirit descends and speaks in the world. The spirit, however, does not speak by itself, but as part of the Trinity. Stanza 5 narrates the awakening of the congregation and its assembly for worship, and in stanza 6 all languages merge into a united “ Hallelujah”, a word generally reserved for angels. The hymn ends with the description of the glory of God's kingdom.The article concludes that Grundtvig’s amalgamation of events, times and opposites in this hymn presupposes a particular conceptualisation of the spirit, and it leaves as an open question that awaits further study whether this conceptualisation of the spirit and hermeneutics is a central feature in many of Grundtvig’s other hymns.